Flow injection analysis with electrochemical detection for rapid identification of platinum-based cytostatics and platinum chlorides in water - Kominkova, Marketa; Heger, Zbynek; Zitka, Ondrej; Kynicky, Jindrich; Pohanka, Miroslav; Beklova, Miroslava; Adam, Vojtech; Kizek, Rene (International journal of environmental research and public health, 2014)
Platinum-based cytostatics, such as cisplatin, carboplatin or oxaliplatin are widely used agents in the treatment of various types of tumors. Large amounts of these drugs are excreted through the urine of patients into wastewaters in unmetabolised forms. This phenomenon leads to increased amounts of platinum ions in the water environment. The impacts of these pollutants on the water ecosystem are not sufficiently investigated as well as their content in water sources. In order to facilitate the detection of various types of platinum, we have developed a new, rapid, screening flow injection analysis method with electrochemical detection (FIA-ED). Our method, based on monitoring of the changes in electrochemical behavior of analytes, maintained by various pH buffers (Britton-Robinson and phosphate buffer) and potential changes (1,000, 1,100 and 1,200 mV) offers rapid and cheap selective determination of platinum-based cytostatics and platinum chlorides, which can also be present as contaminants in water environments.
Keywords: Platinum; platina; Antineoplastic Agents; Flow Injection Analysis; protinádorové látky; sloučeniny platiny; chemické látky znečišťující vodu; průtoková injekční analýza; Water Pollutants, Chemical; Platinum Compounds